2003
DOI: 10.14310/horm.2002.1182
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported prevalence of obesity among 20,329 adults from large territories of Greece, Serbia and Turkey

Abstract: The aim of this study was to investigate the prevalence of overweight, obesity and body mass index (BMI) distribution in people living in large territories of Greece, Serbia and Turkey. A cross-sectional multi-national epidemiological survey was designed on the basis of self-reported information on height and weight using the formula kg/m2. Overall, 20,329 individuals, aged 20-68 yrs, 8,973 males and 11,356 females, participated in the study. Of these, 4,032 were selected from northern Greece, 10,069 from sout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
6

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 11 publications
1
16
0
6
Order By: Relevance
“…Some reports show that the prevalence of obesity is particularly high in adults; however, available epidemiological data are scarce and confi ned to particular geographical areas [4,5] .…”
Section: Introductionmentioning
confidence: 99%
“…Some reports show that the prevalence of obesity is particularly high in adults; however, available epidemiological data are scarce and confi ned to particular geographical areas [4,5] .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, among male conscripts of the Greek army, 28.5% was overweight, and an additional 10.4% was obese [19]. Respective values from a study conducted on the general population of three Balkan countries were 31.4% and 12.4% [20]. Therefore, it is indicated that overweight affects soccer players in a lesser extent than it does the general population.…”
Section: Prevalence Of Overweightmentioning
confidence: 97%
“…Fi zik sel ak ti vi te nin azal ma sıy la bir lik te, ar tan mik tar da sa tü re yağ ve aşı rı şeker kul la nı mı -na yol açan kö tü bes len me alış kan lık la rı obe zi te yi, sa de ce ge liş miş olan ül ke le rin de ğil, tüm dün ya nın yay gın bir so ru nu ha li ne ge tir miş tir. [1][2][3] Fark lı ül ke ler de, eriş kin yaş gru bun da fark lı obe zi te pre va lans la rı bil di ril mek te dir. [2][3][4][5] Eriş kinler de obe zi te pre va lan sı Ba tı Av ru pa ül ke le rin de %10-25, Ame ri ka kı ta sın da ki ül ke ler de %20-35 ara sın da bil di ril mek te dir.…”
Section: Obezite Prevalansı Ve Metabolik Risk Faktörleri Ile İlişkisiunclassified
“…[1][2][3] Fark lı ül ke ler de, eriş kin yaş gru bun da fark lı obe zi te pre va lans la rı bil di ril mek te dir. [2][3][4][5] Eriş kinler de obe zi te pre va lan sı Ba tı Av ru pa ül ke le rin de %10-25, Ame ri ka kı ta sın da ki ül ke ler de %20-35 ara sın da bil di ril mek te dir. ABD 'de yü rü tü len NHA-NES (Na ti o nal He alth and Nut ri ti on Exa mi na ti on Sur vey) 1999-2000 so nuç la rı, NHA NES 1988-1994 so nuç la rıy la kar şı laş tı rıl dı ğın da, ka dın lar da obe zite sık lı ğı %23.4'ten %33.4'e yük sel miş tir.…”
Section: Obezite Prevalansı Ve Metabolik Risk Faktörleri Ile İlişkisiunclassified